Singlet fission preserves polarisation correlation of excitons. Issue 9 (15th February 2023) - de la Perrelle, Jessica M.; Tapping, Patrick C.; Schrefl, Elisabeth; Stuart, Alexandra N.; Huang, David M.; Kee, Tak W.
Abstract : Time-resolved polarisation anisotropy and Monte Carlo simulations show that singlet fission preserves polarisation correlation between photons absorbed and emitted by a material through removing excitons decorrelated by migration. Abstract : Singlet fission (SF) holds the promise to circumvent the photovoltaic efficiency limit to reach a power-conversion efficiency above 34%. SF of TIPS-pentacene (TIPS-Pn) has been investigated but its mechanism is yet to be well elucidated. Recently, we developed a nanoparticle (NP) system, in which doping of TIPS-Pn in a host matrix yields a range of average intermolecular distances, d, to study the dependence of SF in TIPS-Pn on d . At large d values, where the bimolecular SF process should be unfavourable, a relatively high SF quantum yield ( Φ SF ) is still observed, which implies a deviation from a random distribution of TIPS-Pn throughout the NP. Here, using polarisation-sensitive femtosecond time-resolved spectroscopy and Monte Carlo simulations of exciton migration and SF, we quantify the level of clustering of TIPS-Pn in the host matrix, which is responsible for the higher than expected Φ SF . The experimental data indicate a preservation of polarisation correlation by SF, which is uncommon because energy transfer in amorphous materials tends to result in depolarisation. We show that the preservation of polarisation correlation is due to SF upon exciton migration. Although exciton migration decorrelates polarisation, SF acts to remove decorrelated excitons to give an overall preservation of polarisation correlation.